Effect of Hymenolipes nana infection on some blood parameters in some definitive host: Hanan J. N. Al.Awsy , Hayder M. A. Al-Rubaiae ,Ekram A. A. Al-Samarrae - Al.Awsy, Hanan J. N. (The Iraqi Journal of Veterinary Medicine, 2009)
The aim of this study is to determine the effect of Hymenolepis nana infection in some bloodparameters of some final host ( rats & mice ) by experimental infection of 15 rats and 48 mice . Theresults showed that the prepatant period between 12-14 days and the shape of eggs spherical & slightlyellipsoid in mean 40.92 X 35.96 microne & the numbers of eggs in feaces increased with the severityof the infection .The infection which effected on the blood parameters by decreasing the means of packed cell volume ,total white blood count , lymphocytes , while increased the means of neutrophils , monocytes ,eosinophils & basohpils in infected group